Social Analysis of the Trekking Tourism in Taplejung - Luintel, Youba Raj (Academic Voices: A Multidisciplinary Journal, 2019)
This report is about gender and social inclusion including the gender, poverty, caste scenarios of Taplejung regarding the tourism industry. Interviews, key informant interviews, focus group discussions and observations were done in order to solicit primary information. A field visit was made to the Ghunsa trail (up to Lelep) and the Pathivara trail from 8 to 22 July 2012. The main purpose of undertaking the present gender and social inclusion analysis is to explore the diversity profile of Taplejung, one of the Upper Himalayan Trail (UHT) districts, so as to identify the nature of relationships between tourism and disadvantaged groups (DAGs) and get an understanding of poverty and exclusion. This study identifies that the tourism sector in Taplejung carries several risks. Road building is one of them, which has multiple effects.